Os arquivos e sua contribuição para educação patrimonial - PASSOS, Marta Inaura Pantoja (2017)
The work proposes a discussion of the role of the Archives as collaborators of Patrimonial Education in the Schools and Universities, aiming to contribute to the formation of an awareness of valuation and preservation of Cultural and Educational Heritage, and within this framework, what is the participation and contribution of the professional Archivist, if is prepared to work in this context, the position of the bodies responsible for heritage education in Brazil, how to elaborate the methodologies to be implemented, the relationship of archives with that body, schools, universities, and society as a whole and what is being done to make the integration between archives schools, universities and the other professionals who work in this area happens.